Low-Cost Optical Filters Based on SiOxCy:H and Ag Thin Films Fabricated by Plasma Enhanced Chemical Vapor Deposition and Sputtering - Ahmed Kotbi; Michael Lejeune; Pierre Barroy; Ilham Hamdi Alaoui; Wiaam El Hakim; Frederic Lamarque; Andreas Zeinert (Photonics)
Hexamethyldisiloxane (HMDSO) is an organosilicon compound with a modifiable bandgap, depending on the deposition conditions. This material has many unique properties due to its stability, low toxicity, and strong adhesion, making it useful as a protective barrier against corrosion, moisture, and oxidation. In this work, HMDSO films were deposited on glass substrates by the Plasma Enhanced Chemical Vapor Deposition (PECVD) technique at different deposition times. The optical properties of HMDSO films, such as dielectric permittivity, refractive index, extinction and absorption coefficients, and band gap energy, are inferred from transmission and reflection spectra. As the deposition time increased, the real part of the dielectric constant, the refractive index, and the bandgap energy showed a decrease, dropping from 4.24 to 3.40, from 2.06 to 1.84, and from 2.85 eV to 2.03 eV, respectively. The latter result is determined using classical models such as the O’Leary-Johnson-Lim (‘OJL’) interband transition and the harmonic oscillator model. HMDSO and Silver are used in this study for the fabrication of optical filters using two types of structures, a multiple cavity metal–dielectric (MCMD) and the Fabry–Perot structure. The silver layers are deposited by a sputtering process. The MCMD optical filter shows a higher transmittance of about 30%, but a wide range of wavelengths is transmitted. In contrast, the Fabry–Perot filter showed high contrast but a lower transmittance of about 20%.